2017
DOI: 10.1016/j.eurpolymj.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Poly(butylene succinate-ran-ε-caprolactone) copolyesters: Enzymatic synthesis and crystalline isodimorphic character

Abstract: In this paper, the preparation of PBS-ran-PCL copolyesters by enzymatic ring opening polymerization is presented for the first time. The copolyesters were produced in a wide composition range and free of metallic contaminants, so they may be regarded as potential biomaterials. The copolymers have been characterized by proton and carbon nuclear magnetic resonance (1 H and 13 C NMR), gel permeation chromatography (GPC), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), polarized light op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 26 publications
6
62
1
Order By: Relevance
“…Tan et al suggested that such small changes may be attributed to lattice distortions due to the accumulation of excluded commoner at the surface of the crystals, although no specific evidences for such accumulation were provided [15]. However, this interpretation would not be in agreement with the relevant changes in the thermal properties (See Figure 2 and bottom part of Figure 5) observed in these systems, in parallel with the changes in the lattice spacings [4,11,16,19,25]. In fact, several theories of comonomer inclusion in the crystal predict the observed trend of (equilibrium) melting temperatures with composition, as it will be described in a forthcoming section.…”
Section: Co-units Co-crystallization: Unit Cell and Lamellaementioning
confidence: 96%
See 3 more Smart Citations
“…Tan et al suggested that such small changes may be attributed to lattice distortions due to the accumulation of excluded commoner at the surface of the crystals, although no specific evidences for such accumulation were provided [15]. However, this interpretation would not be in agreement with the relevant changes in the thermal properties (See Figure 2 and bottom part of Figure 5) observed in these systems, in parallel with the changes in the lattice spacings [4,11,16,19,25]. In fact, several theories of comonomer inclusion in the crystal predict the observed trend of (equilibrium) melting temperatures with composition, as it will be described in a forthcoming section.…”
Section: Co-units Co-crystallization: Unit Cell and Lamellaementioning
confidence: 96%
“…Deviations from the linear dependence [19,23,25,28] are typically described according to Fox [29] and Gordon-Taylor [30] equations.…”
Section: Pseudo-eutectic Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…PCL is invariably produced by ROP of ɛ‐caprolactone by using either chemical or enzymatic methods. ROP copolymerization of CL with a wide variety of other cyclic monomers has been extensively examined with the purpose of designing PCL copolyesters with improved thermal and mechanical properties . In this sense, the PCL copolyesters containing aromatic units and synthesized by ROP, as they are PCL‐PHT and PCL‐PBT, are particularly noteworthy in the present context.…”
Section: Introductionmentioning
confidence: 99%